Eleven-Year Distribution Pattern of Hepatitis C Virus in Southern Italy. (9th August 2012) - Marascio, Nadia; Matera, Giovanni; Quirino, Angela; Giancotti, Aida; Barreca, Giorgio S.; Lamberti, Angelo G.; Caroleo, Benedetto; Liberto, Maria Carla; Focà, Alfredo
Abstract : Analysis of the Hepatitis C Virus (HCV) genotype spread in a particular area has a crucial impact on public health. In this study, we update information on the distribution of HCV genotypes, by evaluating a hospital-based cohort of 2, 153 chronic hepatitis C patients, collected prospectively among subjects attending University Hospital of Catanzaro, within an area of Southern Italy. We assessed the rates (%) of HCV genotypes during two consecutive periods, from 2001 to 2005 and from 2006 to 2011, according to age and gender. Considering overall observation time, subtype 1b was predominant followed by subtypes 2a/2c, genotype 3 and 4. Statistical evaluation of the age of HCV patients stratified by genotypes, revealed a slight but significant increase in the median age of 1b, 2a/2c and 3 HCV genotype-infected subjects, during the 2006–2011 period, whilst genotype 4 patients exhibited a decrease in the median age during the same period studied. Moreover genotype 4 increased between 2002 and 2003 as well as between 2010 and 2011. Due to the peculiar diagnostic/clinical/therapeutic features of HCV-4, our findings warrant a deeper investigation to better control infections caused by such genotype.